Efek Diet Sodium Pada Penderita Hipertensi : A Systematics Review - Sastra, Komang Budi (E-Jurnal Medika Udayana; Vol 11 No 10 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i10.P06, 2022)
Introduction: Hypertension is a degenerative disease that affects most people in the world. One of the efforts that can be done to reduce high blood pressure is to include sodium intake every day. This study will discuss further about the sodium diet in patients with hypertension. The results: Based on the search results, 4 journals were obtained, with a total population of 396. All studies conducted in the study were located in several countries, namely 1 study in Africa, America, 1 study in America, 1 study in Brazil and 1 other study conducted in China. All studies in this study received interventions in the form of sodium diet and anti-hypertensive therapy in different time frames. There were 180 patients who received anti-hypertensive therapy within 8 weeks and 38 patients received anti-hypertensive therapy within 1 week while on a low salt diet. The percentage of males was 45.2% (n = 179) and female was 54.8% (n = 217). Two studies showed a significant direct result in reducing hypertension, but the other two studies linked a decrease in blood pressure indirectly to the intervention performed. Similar to the population in Indonesia. In the study found that dietary sodium has a lowering effect on blood pressure. Conclusion : Sodium consumption in accordance with standard levels can be used as an effort to prevent primary intake in reducing the risk of hypertension occurring in the future. Keywords : Dietary Approach to Stop Hypertension, Diet Sodium, Hypertension